Bernard–Soulier syndrome caused by a hemizygous GPIbβ mutation and 22q11.2 deletion. Issue 4 (5th August 2013) - Kunishima, Shinji; Imai, Tsuyoshi; Kobayashi, Ryoji; Kato, Motohiro; Ogawa, Seishi; Saito, Hidehiko
Abstract: Background: Bernard–Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by giant platelets, thrombocytopenia, and a prolonged bleeding time, which is caused by homozygous mutations in the GPIbα, GPIbβ, or GPIX genes. The 22q11.2 deletion syndrome (22q11.2DS) is caused by a microdeletion on chromosome 22, which includes the GPIbβ gene, and is characterized by abnormal development of the pharyngeal apparatus and heart. Thus, patients with 22q11.2DS are obligate carriers for BSS. Methods: We evaluated two infants with BSS and performed the genetic analysis of the GPIbα, GPIbβ, or GPIX genes, and investigated the segregation of the mutation within the families. The status of the 22q11.2 deletion was examined by fluorescence in situ hybridization and single‐nucleotide polymorphism array copy number analysis. Results: DNA sequencing analysis revealed that the infants were compound heterozygous for a hemizygous mutation in the GPIbβ gene (p.Trp148X and p.Leu97Phe, respectively) and 22q11.2 deletion in the other chromosome. Both infants had the common 3Mb 22q11.2 deletion but did not show major phenotypic features of 22q11.2DS, such as developmental delay, cardiac defects, dysmorphic facial features, palatal anomalies, hypocalcemia, and immune deficiency. The 22q11.2DS would not have become clear if detailed molecular genetic analyses of BSS had not been performed. Conclusions: Our cases illustrate that a suspicion of 22q11.2 deletion is warranted in pediatric BSS patients with a mutation in the GPIbβ gene, even without remarkable symptoms.